Using Trauma Theory to Explain the Victim-Offender Overlap and Examining Its Relevance in Sentencing - McLachlan, Katherine J. (Victims & offenders, 2025)
People who offend often have a history of crime victimization. Various victimization theories over the past century have been developed to explain why some people are both victims and offenders. To examine the association between victimization and offending, trauma theory is compared to popular victimization theories. Content analysis of a sample of 20 published South Australian sentencing remarks of adults identified as “victim-offenders” is then undertaken to examine how judges understand the victim-offender overlap and respond to “victim-offenders.” A key sentencing consideration is the “general background” of a defendant, which includes experiences of victimization. By examining how sentencing judges acknowledge crime victimization in the lives of defendants and the theories that best explain sentencing responses to “victim-offenders,” recommendations are made for more effective sentencing of people identified as victim-offenders.